Participação do cliente cirúrgico no processo terapêutico: "estudo sobre estratégias de assistência de enfermagem" - Rocha, Terezinha de Jesus (1990)
This study searches ways of nursing' interventions and its participation in the terapeutic process near the hospitalized Client. Theoreticaly some concepts are established, such as the selfcare and the participation tcward protection/recuperation of health. The methodology utilizes the interview tecimique to obtain the data. The sample corresponds to 105 hospitalized clients and 50 R. Nurses who assist hospitalized clients in 2 University Hospitais of Rio de Janeiro City. The conclusion of the study indicates some omissions not only in the general nursing'actuation related to the clients' preparation during its intemation as in the participation nurse/client in the terapeutic process. It is concluded also that: 1) in the interaction nurse/client the human factors are not being considered and 2) the work conditions are interfering negatively in the nursing' assistence. It is recomended: a) to develop the in-service- education on the subject; b) to realize studies to deep the kncwledge about the interactive and the psychotherapeutic phenomena; c) to improve the methodology of nursing assistence toward the selfcare and d) to develope strategies toward the integration among agencies of nursing' formation and institutions of nursing' employment.